Agro-Morphological Traits and Molecular Diversity of Proso Millet (Panicum miliaceum L.) Affected by Various Colchicine Treatments - Aiym Zeinullina; Meisam Zargar; Elmira Dyussibayeva; Aidyn Orazov; Irina Zhirnova; Gulzat Yessenbekova; Lyudmila Zotova; Aiman Rysbekova; Yin-Gang Hu (Agronomy, 2023)
Colchicine is a substance used to induce mutations in order to regulate important agronomic traits. The genotypes Pavlodarskoe 4, Quartet, and PI 289324, originating from Kazakhstan, the Russian Federation, and Hungary, respectively, were used as materials. The objective of this study was to investigate the effects of different colchicine concentrations (0.0, 0.04, 0.06, 0.08, and 0.1%) and treatment times (6, 12, and 24 h) on the agronomic traits of proso millet (Panicum miliaceum L.) and to assess the genetic diversity of the M2 generation using inter simple sequence repeat (ISSR) markers. The experiment was conducted in 2021 for the M1 generation and in 2022 for the M2 generation, from May to September. The percentage of field germination decreased with increasing colchicine concentrations and exposure durations. The mean field germination percentages were 48.57% in Pavlodarskoe 4, 43.28% in Quartet, and 53.14% in PI 289324 under colchicine treatment. Chlorophyll-defective M1-M2 plants were obtained using various colchicine concentrations and exposure periods. The highest number of mutational modifications was attained with the 0.08–0.1% concentrations of colchicine. Based on the research results, a total of 248 plants with chlorophyll-defective mutations were selected from 2214 plants. The growing seasons of M1 and M2 plants were shortened by higher colchicine concentrations (0.08–0.1%) combined with soaking times of 12 and 24 h. Thus, the longest growing season (84 days) was observed with a 6 h treatment time for PI 289324, while the shortest (78 days) was recorded for 12 and 24 h treatments. The possibility of obtaining morphological mutations using colchicine has been confirmed. The ISSR primers amplified a total of 1333 fragments; 1281 bands were found to be polymorphic, and 52 bands were monomorphic. The percentage of polymorphism varied from 80 to 100%, with an average of 96.11%. Most of the different allelic bands were detected when applying the 0.08% colchicine concentration. These positive variations are a great opportunity to use colchicine as a tool for improving agronomic traits in plant breeding.